Insights into solid dosage forms with nonlinear optical imaging - Tomberg, Teemu; Arbiol Enguita , Alba Maria; Strachan, Clare J. (Journal of Medical Science, 2023)
Microscopic chemical and solid-state structures and their changes in solid drugs and dosage forms can profoundly affect pharmaceutical performance and patient safety. Despite this, their detailed spatially-resolved analysis can be difficult or impossible with established analytical technologies. Multimodal non-linear optical imaging presents opportunities for sensitive and specific chemical and solid-state pharmaceutical imaging. Non-linear optical imaging encompasses several nonlinear optical phenomena, including coherent anti-Stokes Raman scattering (CARS), stimulated Raman scattering (SRS), and sum frequency/second harmonic generation (SFG/SHG). Imaging in 3D with (sub)micron resolution is rapid, non-destructive, possible in situ in aqueous media, and generally does not require prior sample preparation. This mini-review explores several applications of non-linear optical imaging for solid drug and dosage form analysis.